Development of milk replacer for rearing kids (Bangladesh Veterinarian, 2015)
The present study was conducted to evaluate the effect of different milk replacers on the performance of kids. In a 60-day feeding trial, twenty kids of both sexes (15 days of age and average 1.9 ± 0.4 kg BW) were divided into four groups having five kids in each and were assigned to four treatments: milk replacer prepared using shoti (Curcuma zedoaria) powder (T1), milk replacer prepared using fresh eggs and wheat flower (T2) and milk replacer prepared from skim milk powder (T3). Total DM and milk DM intake were significantly (P